RNA-Seq reveals transcriptomic interactions of Bacillus subtilis natto and Bifidobacterium animalis subsp. lactis in whole soybean solid-state co-fermentation - Wang H.K. (Academic Press, 2016)
10.1016/j.fm.2015.04.012